2023
DOI: 10.3389/fpls.2022.1058092
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungus alleviates anthracnose disease in tea seedlings

Abstract: Tea has been gaining increasing popularity all over the world in recent years, and its yield and quality depend on the growth and development of tea plants [Camellia sinensis (L.) Kuntze] in various environments. Nowadays, biotic stress and extreme weather, such as high temperature, drought, waterlogging, pests, and diseases, bring about much pressure on the production of tea with high quality. Wherein anthracnose, which is the most common and serious disease of tea plants, has earned more and more attention, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
3
4
1
Order By: Relevance
“…It was found that these mycorrhizal colonization related genes, RAM2 ( LOC114297081 ), STR ( LOC114323273 ) and STR2 ( LOC114276941 ), were only significantly up-regulated in the cuttings at the S2 stage ( Supplementary Data 1 ) compared with the control in the second experiment of this study. And it was supposed that ARs have started to establish mycorrhizal symbiosis with AMF, which is consistent with our previous observations in the roots of mycorrhizalized tea seedlings ( Chen et al., 2023 ). All these results could indicate that the presence of AMF in the cutting substrate or root of cuttings, making it possible to further analyze how AMF affects the rooting of tea cuttings.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It was found that these mycorrhizal colonization related genes, RAM2 ( LOC114297081 ), STR ( LOC114323273 ) and STR2 ( LOC114276941 ), were only significantly up-regulated in the cuttings at the S2 stage ( Supplementary Data 1 ) compared with the control in the second experiment of this study. And it was supposed that ARs have started to establish mycorrhizal symbiosis with AMF, which is consistent with our previous observations in the roots of mycorrhizalized tea seedlings ( Chen et al., 2023 ). All these results could indicate that the presence of AMF in the cutting substrate or root of cuttings, making it possible to further analyze how AMF affects the rooting of tea cuttings.…”
Section: Discussionsupporting
confidence: 91%
“…We speculated that this may be related to the effect of exogenous auxin on the symbiosis establishment between AMF and root. In the first experiment, IBA treatment significantly promoted the infection of AMF on the roots of ‘Pingyangtezao’ cuttings (46.29%, Table 2 ), which was higher than our previous mycorrhizal experiments on tea plant ( Chen et al., 2021 ; Chen et al., 2023 ). Same results were also found in the other two varieties, but did not reach a significant level.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Symbiosis between plants and microorganisms occurs wide in natural ecosystems, affects plant terrestrializations (Puginier et al, 2022), evolution (Batstone, 2022;van Galen et al, 2023), and tolerance to abiotic and biotic stress (Zeng et al, 2022), and widens the habitability ranges of plants (Muñoz and Carneiro, 2022). Among all the beneficial microorganisms symbiosing with plants, five families of microorganisms have been greatly paid on attentions, i.e., arbuscular mycorrhizal fungi (Kaur et al, 2022;Razak and Gange, 2023;Chen W. et al, 2023), ectomycorrhizal fungi (Karlsen-Ayala et al, 2022;Jörgensen et al, 2023;Xiao et al, 2023), root endophytic fungi (Manzur et al, 2022;Sun et al, 2022;Qin et al, 2023), dark septate fungi (Gaber et al, 2023;Wang et al, 2023;Chen S. et al, 2023), and plant growth-promoting rhizobacteria (PGPR) (Ahmad et al, 2022;Gowtham et al, 2022;Zhao et al, 2023). These beneficial microorganisms show strong effects on their plant hosts under drought stress (Ahmad et al, 2022;Gowtham et al, 2022;Zhao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%